(untitled) (Південний архів (історичні науки), 2022)
The purpose of the article is to investigate the significance of official holidays and ceremonies in the formation of a “new human” on the territory of Soviet Ukraine in the interwar period, to determine their characteristics and means of influencing the consciousness of the population. Research methods. The achievement of the goal and objectives of the research became possible due to the use of general scientific and specific historical methods of scientific research. Among them, the application of the method of analysis and synthesis is the leading one, which made it possible to find out the general features of the new communist holidays of Soviet Ukraine in the outlined period on the basis of the study of individual components. Successful solution of research problems would be impossible without the application of the principle of historicism. The scientific results lies in a comprehensive coverage of the role and importance of created and implemented during the 20–30’s of the XX century communist rites for the formation of a “new human” and the creation on this basis of a holistic picture of socio-cultural and political life in Soviet Ukraine in this period. The peculiarities of the introduction of Bolshevik holidays in the republic and their influence on the consciousness of its inhabitants are determined. The examples illustrate the attitude of people to new rites and holidays. The main plots and scenarios of celebrating such events have been clarified. All of them had one goal – to propagate communist ideology, so there is a noticeable trend of dependence of the introduction of Soviet rites on the political situation and party tasks in a particular historical period. Conclusions. After the capture of Ukraine, one of the priorities of the Moscow communist leadership was to form a “new human” on its territory, loyal to the government and devoid of national characteristics. To carry it out, unprecedented communist agitation and propaganda was launched, one of the most effective components of which was the creation of a new socialist/communist rite. The Soviet holidays were to displace the traditional worldview and values from the cultural memory of the people of Ukraine and replace them with new ones related to Bolshevik ideology and doctrine. Their planting had not only an educational effect, but also gradually created the illusion of belonging to an imaginary single community of “Soviet people” – the “most progressive” part of humanity.